Identification of low levels of neutral and functional genetic diversity in South African bontebok (Damaliscus pygargus pygargus) - Martin Ratanang Mogakala; Rae Marvin Smith; Caswell Mavimbela; Desiré Lee Dalton (Ecology and Evolution, 2024)
Abstract Bontebok (Damaliscus pygargus pygargus) and blesbok (D. p. phillipsi) are classified as separate sub‐species. The blesbok has a widespread distribution throughout South Africa and is listed as least concern by the International Union for Conservation of Nature (IUCN) Red List of Threatened Species. Bontebok on the other hand is endemic within the Cape Floristic Region of the Western Cape in South Africa and has been listed as near‐threatened species on the IUCN Red List of Threatened Species. Bontebok populations experienced a severe bottleneck and were brought back from the brink of extinction in the 1830s. Currently, the subspecies is threatened by hybridisation with blesbok resulting in fertile offspring. To date, molecular investigations using neutral markers have determined that genetic diversity in pure South African bontebok was significantly lower than in pure blesbok. Here, we investigated genetic diversity in bontebok, blesbok and hybrid individuals using microsatellites and an adaptive marker (toll‐like receptor two (TLR2)). The study of single nucleotide polymorphisms (SNPs) revealed five mutations in TLR2 in different individuals and subspecies of D. pygargus. This included three non‐synonymous and two synonymous mutations. The three amino acid substitution mutations were predicted to have no effect on protein function. Two of the five mutations, one of which resulted in an amino acid substitution, were not present in bontebok. The other three mutations were present to varying frequencies in the three groups. We confirm low adaptive and neutral diversity in bontebok. These mutations provide insights into the genetic diversity and relationships among the two sub‐species of D. pygargus and may have implications for their conservation and management.